Research on Trajectory Planning of Fermented Grains Grasping Mechanical Arms - Xuan Liu; Zhaomin Wu; Chang Wang; Jianhua Zhang (Jixie chuandong)
The discharging work of fermented grains is a necessary process in the production of wine， the difficulties in automating the work with mechanical arms include the long and narrow working space and the loose form of fermented wine which tends to fall. The working space is long and narrow， and the end of the grab needs to be grabbed multiple times. Being easy to spill， it is necessary to ensure the tightness of the grasping end and the controllability of the posture of the grasping end during the movement after grasping， etc. Aiming at the problem that multiple grabbing is required for the discharging work， a joint division strategy is proposed. According to the importance of the joints， the joint types are divided and the appropriate number of trajectory planning algorithms is selected. On the premise of satisfying the operating performance of the manipulator， the computational difficulty of each grasping planning is reduced. For the tightness requirements of the grab end， a grasping end is designed to ensure that the bottom is closed. Aiming at the requirement of attitude controllability during operation， an attitude adjustment model is established and the controllability of the end posture of the manipulator in joint space based motion planning is improved.